Effect of flood plain embankments on channel scour / Elias Mohd Den - Mohd Den, Elias (2002)
A study has been conducted to investigate the effect of embankment constriction of a flood plain on localized scour in the main channel using a physical hydraulic model large enough to avoid scale effects of surface tension, gravitational affects and viscous forces. The physical river model considered is composed of mobile bed-channel filled with fine gravel (d5o = 2.5mm), flood plains with rigid bed and 70° skewed embankments. The study revealed that no scour occurred if the constriction on the flood plains or of embankments was less than 65% and in all cases the scouring started to occur when the velocity in the main channel reached a value of 0.62m/s which can be considered the threshold velocity of the fine gravel for the flow depth of 210mm. The results have also shown that the scour attained a maximum depth at a point where the velocity is maximum and there seems to be a definite relationship between maximum scoured depth, (D+ds)/D and the amount of constriction (m), provided m ≥ 70%.